2020
DOI: 10.1016/j.jcv.2020.104684
|View full text |Cite
|
Sign up to set email alerts
|

Analytical sensitivity and clinical sensitivity of the three rapid antigen detection kits for detection of SARS-CoV-2 virus

Abstract: Highlights We compared analytical sensitivity and clinical sensitivity for the three commercially available rapid antigen detection (RAD) kits for detection of SARS-CoV-2 virus. The three RAD kits varied 102 to 105 fold less sensitive than RT-PCR. Clinical sensitivity of RAD kits ranged from 22.9% to 71.4% for detecting respiratory specimens from COVID-19 patients. Understanding the clinical characteristics of different RAD kits can incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
85
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 13 publications
19
85
1
Order By: Relevance
“…For Ct values <25, the sensitivity increased above 95% [ 8 ]. The same conclusion was found by Mak et al, using only 35 specimens [ 17 ]. The lower sensitivity observed with higher Ct values is in line with our evaluation ( Table 2 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…For Ct values <25, the sensitivity increased above 95% [ 8 ]. The same conclusion was found by Mak et al, using only 35 specimens [ 17 ]. The lower sensitivity observed with higher Ct values is in line with our evaluation ( Table 2 ).…”
Section: Discussionsupporting
confidence: 88%
“…In the literature, we identified at least four studies that evaluated the Panbio COVID-19 Ag rapid test [ 8 , 12 , 14 , 17 , 22 ]. In a population of 341 patients, Fenollar et al found a specificity of 94.9% and a good sensitivity but only for samples with Ct values <25 (i.e., 94.2 to 100%) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous commercial assays are now available [ 5 ], but there are limited data on their clinical performance. Based on previous studies, the sensitivity of SARS-CoV-2 Ag-RDTs range between 22.9% and 93.9% when compared to rRT-PCR [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Apart from sensitivity, it is important that such tests identify potentially contagious individuals to reduce SARS-CoV-2 transmission.…”
Section: Introductionmentioning
confidence: 99%